(untitled) (Tazakka: Jurnal Pendidikan dan Keislaman, 2024)
The teacher, as the forefront of education, plays a crucial role in shaping the future of the younger generation. They are not only educators but also guides, motivators, and role models for their students. Therefore, the quality of a teacher significantly determines the quality of education. One of the efforts by the Indonesian government to enhance the quality of teachers is through teacher certification. However, this endeavor has not yielded optimal results yet. This research aims to analyze the teacher certification program in improving the quality of Islamic education. The study employs a literature review (library research) with a qualitative approach. Data sources are obtained through an in-depth examination of various literature materials such as books, articles, journals, and other supporting sources. The research findings reveal that the teacher certification program in enhancing the quality of Islamic education encounters several new challenges: (1) the portfolio system poses difficulties for teachers in remote areas with limited access to training, seminars, and other activities; (2) the Pre-Service Professional Teacher Education (PLPG) model, which often makes teachers overly occupied with certification requirements, leading to neglect of the teaching and learning process in schools; (3) the Teacher Professional Education (PPG) model, which exhibits a clear inconsistency as it treats non-educational bachelor’s degree (DIV) graduates and bachelor’s degree (S1) graduates on the same level through PPG.